We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
42
1
avatar

Solve x^2 - abs(4x - 2) + 5 = 0.

 Oct 27, 2019
 #1
avatar+199 
0

x^2 - |4x - 2| + 5 = 0

x^2 - |4x - 2| = -5 

 

Break it down into equations

 

x^2 - ( 4x - 2 ) = -5  ------> apply quadratic formula; x = 2 + sqrt(3)*i, x  = 2 - sqrt(3)*i

x^2 - ( - ( 4x - 2 ) = -5 ----> apply quadratic formula; x = - 2 + sqrt(3)*i, x = -2 - sqrt(3)*i

 

And there you have it. Seventh grade skillz!

 Oct 27, 2019

25 Online Users

avatar
avatar